Catalytic Enhancement of Gmelinol Yield from Gmelina arborea Leaves: Process Optimization and Reproducibility - Haruna Ibrahim; Abubakar M. Ali; Mohammed Danjuma Jibrin (Science Tech Group, 2026)
Gmelinol, a bioactive lignan derived from Gmelina arborea, exhibits significant antimicrobial, antioxidant, anti-inflammatory, and antidiabetic properties. Despite its pharmacological potential, existing extraction methods are largely qualitative, poorly reproducible, and lack quantitative yield metrics. This study addresses these gaps by developing a reproducible and statistically validated catalytic process for gmelinol production from Gmelina arborea leaves using barium chloride-catalyzed thermal hydrolysis. The effects of reaction time (10-50 min) on gmelinol yield were systematically investigated at 80 °C. Optimal conditions were identified at 40 min, yielding 17.90% (437.12 mg/g) of gmelinol with excellent reproducibility (coefficient of variation = 3.95%). Statistical analyses, including paired t-tests and one-way ANOVA, confirmed that reaction time significantly influenced yield (p<0.001), while Tukey HSD post-hoc tests validated 40 min as the optimal duration. Prolonged reaction times led to yield reduction, indicative of product degradation. This work provides the first quantitative, mass-based yield benchmark for gmelinol extraction, establishing a reliable and scalable catalytic route that enhances both efficiency and reproducibility. The findings support the sustainable valorization of G. arborea leaf biomass for pharmaceutical and industrial applications.